Systematic reviews of self-pruning incidents on commercial horticulture plants - Elda Kristiani Paisey; Edi Santosa; Deden Drajat Matra; Ani Kurniawati; Supijatno Supijatno; Besse Amriati; Siti Halimatus Sadiyah; Hayu Siwi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Pruning is a crucial practice in horticulture to maintain tree health, reduce production costs, and improve yield. However, conventional pruning remains labor-intensive and costly. Self-pruning has the potential to provide a sustainable alternative, yet studies on its mechanisms and applications in horticultural crops are still limited. This review aimed to systematically synthesize the mechanisms, incidence, and potential applications of self-pruning in horticultural crops. The review followed the PRISMA 2020 framework to ensure transparency and minimize bias. Literature searches were conducted in ScienceDirect and Garuda databases using the keywords self-pruning, pruning, cladoptosis, autophagy, and senescence in both English and Indonesian. The search was restricted to articles published within the last 10 years (2013–2022). Inclusion criteria were original research or review articles on self-pruning in plants. Exclusion criteria were duplicate records, articles from irrelevant fields, non-systematic studies, and grey literature. Bias reduction was addressed by predefined criteria, time limits, specific keywords, and independent screening by two reviewers. From 5,588 records identified, only 25 articles met the inclusion criteria. However, none of the eligible studies specifically addressed self-pruning in horticultural crops. The limited number of relevant articles was due to restricted database coverage and the absence of standardized quality assessment tools within the PRISMA framework. This review highlights a critical research gap on self-pruning in horticultural crops. Broader database searches and the development of standardized quality assessment tools are required. Evaluating the incidence and mechanisms of self-pruning in commercial horticultural crops is essential as a new perspective to support sustainable horticultural production. Keywords: autophagy; abscission; cladoptosis; programmed cell death; senescence